Antiferromagnetic monolayer MnC2 with density functional theory prediction. (3rd April 2018) - Zhang, Bingwen; Zhang, Qinfang; Bai, Yujie
Abstract: A new monolayer MnC2 was predicted as a stable 2D material associated with the result of phonon and AIMD calculations. The in-plane young's modulus is 73.6 N m −1, which is about 20 % of graphene. The monolayer MnC2 is antiferromagnetic with a Néel temperature around 280 K and from the Dirac point of the electronic band we got the fermi velocity of 5.37 × 1.0 5 m s −1 showing excellent electronic transport property. The MnC2 sheet also possesses a promising application as an anode material in lithium ion battery.